Molière in Ragusan Manuscripts - Bratičević, Irena; Lupić, Ivan (Molière u hrvatskoj kulturi, 2024)
Discussions of the rich reception history of Molière in old Ragusa (Dubrovnik) are made possible above all by a single act of manuscript assembly that took place already in the eighteenth century. Without this act, which served as the basis for the printed editions of the Ragusan adaptations of Molière in both the nineteenth and the twentieth century, our knowledge about the fascinating encounter between French and Croatian literary and theatrical cultures would be as fortuitous, haphazard, and inevitably unsystematic as is most of our knowledge that depends on dispersed and disconnected manuscript evidence. Who and why gathered in one place the Ragusan adaptations of Molière? Who arranged to have them copied by a single scribe in five manuscript volumes that still serve as the exclusive basis for modern editions? What have been the fortunes of these manuscript volumes and where are they to be found today? This article endeavors to furnish archivally informed if at times only partial answers to these questions. Special attention is paid to the life and work of the Ragusan citizen Nikola Agić (1708–1757), who is identified as the scribe responsible for copying all the five volumes of the Ragusan Molière.